Formic acid-mediated liquefaction of chitin. Issue 18 (21st June 2016) - Zhang, Jiaguang; Yan, Ning
Abstract : We report pure formic acid-mediated liquefaction of chitin for the first time. Abstract : We report pure formic acid-mediated liquefaction of chitin for the first time. Formic acid exhibited a remarkable ability in the functionalization and depolymerization of ball-milled chitin as well as proto-chitin in raw shrimp shells. Up to 60% combined yield of a series of structurally identified monomeric products was obtained after reaction at 100 °C for 12 h. The product stream could also converge to a single compound, 5-(formyloxymethyl)furfural (FMF), in 35% yield after a longer reaction time. The product evolution was monitored by electrospray ionization mass spectrometry (ESI-MS), and the key finding is that the liquefaction involves several major chemical events in the following sequence: (1) the process starts with partial formylation of the hydroxyl groups in chitin side chains generating soluble polymeric derivatives; (2) formic acid catalyzes polymer chain breakage in a non-conventional, non-hydrolytic pathway forming dehydrated monomers and oligomers; (3) as formylation continues, water accumulates in the system, which induces more monomer and oligomer generation via hydrolysis, and the formation of rehydrated products. As such, water is constantly generated via formylation and subsequently consumed in hydrolysis and rehydration, making the process a self-sustained one.